The “Low House” and the “House with a Mezzanine” — Two Models of the “Russian World” in Sergei Esenin’s Work - Maxim V. Skorokhodov (Studia Litterarum)
Using the example of Sergey Esenin’s work, the article explores two key models of the “Russian world”: the landowner and peasant estates, in which a peculiar culture developed. For Esenin, the most important source of information about life in the estate was Russian literature. The future poet studied the works of Russian writers both at school and independently. Esenin was guided by the traditions of Russian classical literature and the works of contemporary authors. For the poet, the aesthetic significance of gardens and parks, associative relations between trees and people were important. There are often are trees outside the window of the house of a protagonist, a scenery to be found in of both landowner and peasant estates. The Anna Snegina poem is the most striking work of Esenin where the estate-writing traditions of Russian classics were innovatively embodied in all their fullness and diversity. The article examines the processes of transformation and death of the two models of the “Russian world” in the course of wars and revolutions on the example of this poem.